2019
DOI: 10.3390/ijms20163962
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Ca2+ Signaling, Angiogenesis and Vasculogenesis: Just What It Takes to Make a Blood Vessel

Abstract: It has long been known that endothelial Ca2+ signals drive angiogenesis by recruiting multiple Ca2+-sensitive decoders in response to pro-angiogenic cues, such as vascular endothelial growth factor, basic fibroblast growth factor, stromal derived factor-1α and angiopoietins. Recently, it was shown that intracellular Ca2+ signaling also drives vasculogenesis by stimulation proliferation, tube formation and neovessel formation in endothelial progenitor cells. Herein, we survey how growth factors, chemokines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
149
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(154 citation statements)
references
References 323 publications
(645 reference statements)
4
149
0
1
Order By: Relevance
“…Furthermore, phosphatase and tensin homolog (PTEN) regulates TRPC6 activation and subsequent promotion of angiogenesis in primary human pulmonary artery endothelial cells (HPAEs) [118]. As several comprehensive reviews regarding TRP channels and angiogenesis have recently been published, we recommend the readers to turn to these for further information [119][120][121].…”
Section: Trpc Channels and Angiogenesismentioning
confidence: 99%
“…Furthermore, phosphatase and tensin homolog (PTEN) regulates TRPC6 activation and subsequent promotion of angiogenesis in primary human pulmonary artery endothelial cells (HPAEs) [118]. As several comprehensive reviews regarding TRP channels and angiogenesis have recently been published, we recommend the readers to turn to these for further information [119][120][121].…”
Section: Trpc Channels and Angiogenesismentioning
confidence: 99%
“…The pharmacological manipulation of the Ca 2+ response to low (i.e., 20 µM) and high (i.e., 300 µM) doses of ATP strongly suggested that SERCA-dependent Ca 2+ removal from the cytosol is compromised in in situ aorta of OZDF rats. The inhibition of SERCA-dependent Ca 2+ clearance could be due to the down-regulation of SERCA2B, the main endothelial SERCA isoform [46], and/or to the slowing down of its activity. Previous work has revealed that, while SERCA2 protein is up-regulated by type 2 diabetes mellitus, its clearing rate may be severely compromised.…”
Section: Serca2b Protein Is Up-regulated In In Native Aortic Endothelmentioning
confidence: 99%
“…Endothelial cells line the inner lumen of blood vessels and are, therefore, exposed to a myriad of chemical (e.g., growth factors and chemokines) and physical (e.g., laminar shear stress and pulsatile stretch) cues, which must be properly perceived for the maintenance of tissue homeostasis (Moccia et al, 2012a(Moccia et al, , 2019b. TRP channels represent the most suitable signal transduction pathway whereby vascular endothelial cells integrate such a vast array of extracellular stimuli due to the versatility of their gating mechanisms.…”
Section: Trp Channels In Endothelial Cellsmentioning
confidence: 99%
“…Endothelial TRP channels have long been associated to angiogenesis and vascular remodeling due to their ability to engage intracellular signaling pathways associated to endothelial cell proliferation, migration, adhesion, tubulogenesis, and permeability (Moore et al, 1998;Fantozzi et al, 2003;Cheng et al, 2006). Endothelial TRP channels may control angiogenesis by mediating Ca 2+ entry in response to extracellular growth factors, such as VEGF and bFGF, that are liberated in peripheral circulation upon an ischemic insult or by growing tumors (Moccia et al, 2019b). Alternately, TRP channels sense cellular stress factors, such as an increase in ROS production or a decrease in Mg 2+ levels, or an increase in laminar shear stress, which ultimately stimulates arteriogenesis (Moccia and Guerra, 2016).…”
Section: Endothelial Trp Channels Regulate Angiogenesis and Arteriogementioning
confidence: 99%
See 1 more Smart Citation